2018
DOI: 10.1108/ijphm-03-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

The art of building initial trust in medical services

Abstract: Purpose The purpose of this study is to investigate the antecedents of the patient’s initial trust in the doctor. In this sense, it is proposed that trust in the hospital plays a mediating role in the relationship between the physical evidence in the service environment and the patient’s initial trust in the doctor. Design/methodology/approach Two experimental studies with factorial between-subjects design with random assignment were used. The data were analyzed through an analysis of variance. Findings Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…It has been found that interpersonal recommendation is the main factor influence the trust building in prior researches. Such as, Terres and Basso (2018) found that the positive recommendation from the friends, family, healthcare plan and other doctors have a significant effect on initial trust in doctor [50]. Thus, we stated the following: Hypothesis 3.…”
Section: Doctor's Initial Trust Formation Processmentioning
confidence: 75%
“…It has been found that interpersonal recommendation is the main factor influence the trust building in prior researches. Such as, Terres and Basso (2018) found that the positive recommendation from the friends, family, healthcare plan and other doctors have a significant effect on initial trust in doctor [50]. Thus, we stated the following: Hypothesis 3.…”
Section: Doctor's Initial Trust Formation Processmentioning
confidence: 75%
“…In connection with medical treatment, patient trust is defined as a set of belief about the physicians' behavior based on the previous expectations about skills, empathy, privacy, confidentiality, and expertise. According to literary research, a situation where an individual has never had any previous experience with another parties prior to their first meeting is referred to as initial trust (Terres & Basso, 2017).…”
Section: Trustmentioning
confidence: 99%
“…It comprises traits such as willingness to depend on service providers, including the capacity to improve the service and to communicate, confidentiality in practices and reliability of delivery and trade. Terres and Basso (2018) suggest that the confidence and beliefs of patients about the openness, confidentiality, reliability and dependency of the interaction can be influenced by the surrounding environment.…”
Section: 27mentioning
confidence: 99%